Konsep Tasawuf Sunni: Mengurai Tasawuf Akhlaqi, Al-Maqamat dan Ahwal, Al-Ma’rifah dan Mahabbah Perspektif Tokoh Sufi Sunni - Hanifiyah, Fitriyatul (Universitas Nurul Jadid, 2019)
Abstract: Sufism is self-cleansing and the human soul for the means to draw closer to God Almighty. The development of Sufism today can not be separated from the tendency of spiritualism. we cannot ignore that there are two very important technical terms namely maqamat and ahwal in Sufism. To reach the position of maqamat and ahwal the stages must be passed by a Sufi. Achievement at the highest station can be realized in the form of behavior changes or commendable morals. That character will deliver a Sufi to the level of mahabbah and ma'rifah. The research method used in this research is the study of literature (Library Research). For the results of this study that Sufism is a pattern of Sufism Sufism whose teachings go back to the Qur'an and Sunnah. Maqam and hal are a way to achieve the ideal of the Sufis. Through the process of purification of the soul against the tendency of matter to return to the light of God. When God manifests himself in the soul and clean heart of man in both His majesty and beauty, a person will love the manifestation and feel certain joys, heart feels close (qurb), love (mahabbah), raja’ , serenity and sense sure.These mental conditions are called ahwal. Keywords: Sufism, Maqamat and Ahwal, Mahabbah and Ma’rifah